FRI0149 Nocturnal hypertension in ra: a possible association with cardiovascular events. (23rd January 2014) - Hamamoto, K.; Yamada, S.; Yoda, M.; Yoda, K.; Tsuda, M.; Okamoto, K.; Goto, H.; Inaba, M.
Abstract : Background: Although cardiovascular mortality is increased in RA patients relative to the general population, the reasons for high prevalence of cardiovascular events in RA patients is not completely understood. On the other hand, nocturnal hypertension is also known as an important independent predictor of cardiovascular events. However, little is known regarding the relationship between nocturnal hypertensionand RA. Objectives: To examine the association between nocturnal hypertension and RA, and to investigate whether improvement of RA disease activities aftermedical treatment will affect nocturnal hypertension. Methods: A total of 70 patients with active RA (12 men and 58 women), mean age of 68.5 years, were enrolled. Of these patients, 14 patients were evaluated the change of nocturnal blood pressure before and after RA treatment. Nocturnal hypertension was assessed by 24 hours ambulatory blood pressure monitoring. There are four subtypes of nocturnal hypertension. These subtypes are determined by the value of the degree of nocturnal blood pressure decline(%). It was calculated as 100 × [1−sleep SBP/awake SBP]. In normal subjects, the degree of nocturnal blood pressure decline from 10% to 20% is described as dipper. A variety of abnormal diurnal variation patterns are described with the degree of nocturnal blood pressure decline as follows, >20%: extreme-dippers; <10%: non-dippers; and <0%: risers. Results: The mean DAS28-ESR level was 5.6 in 70 RA patients and the mean degree of nocturnal blood pressure decline was 4.5%. The distribution of dipping patterns was as follows: extreme-dippers, 2.9%; dippers, 27.1%; non-dippers, 41.4%; and risers, 28.6%. In simple regression analysis, DAS28-ESR level and the degree of nocturnal blood pressure decline were negatively correlated (p = 0.0042, r = -0.343). In multiple regression analysis, significant independent contributors to the degree of nocturnal blood pressure declinewere age(β = -0.342, p = 0.005) and DAS28-ESR (β = -0.297, p = 0.0210). In 14 RA patients, the mean DAS28-ESR level was improved from 6.1 to 4.6 (p <0.001 ) and the mean degree of nocturnal blood pressure decline was elevated from 1.8 to 8.9 (p = 0.022) after RA treatment. Conclusions: Our data demonstrate that the degree of nocturnal blood pressure decline is blunted in active RA patients. It is suggested that the occurrence of nocturnal hypertension might be one of cardiovascular risk factors in RA patients. References: Ann Rheum Dis 2005; 64 :1595-601 JAMA 1999; 282: 5 Disclosure of Interest: None Declared